Electrochemical behavior of nickel oxide nanoelectrocatalyst in diverse electrolytic environments and its application as an effective electrode for supercapacitors - Chauhan M.; Bangwal A.S.; Borodianskiy K.; Mishra K.K.; Singh P. (My University, 2025)
Electrochemical investigations demonstrate that the nickel oxide (NiO) thin films exhibit superior oxygen reduction reaction activity across various electrolyte media. To produce nanostructured NiO, a sol-gel method was employed, followed by thin film fabrication through spin coating with varying numbers of depositions. The film's structure and morphology were confirmed by XRD and SEM, respectively, while AFM confirmed the deposition of a thin film with an appropriate thickness on the substrate. The electrochemical performance of the electrode was evaluated using cyclic voltammetry, revealing that a specific number of deposited NiO thin films exhibit superior performance compared to others. The superior electrocatalytic activity of nickel oxide is correlated with the various steps involved during the charge transfer in the OER mechanism. Optimization of the operating pH of the proposed electrodes was also carried out in this study. Additionally, these electrodes demonstrated a higher specific energy of 15.5 Wh kg−1 at a specific power of 151 W kg−1 proving their suitability as an electrode material for supercapacitors. © 2023 Elsevier Ltd